Subarea tree routing algorithm based infrastructure for mobile ad-hoc networks - Kamal Khorsheed, Omeed; Abdul Hanan Abdullah, Prof Dr (Journal of Advanced Computer Science & Technology, 2019)
Ad hoc networks are self-organizing and multi-hop networks for data communication. Subarea Tree Routing (STR) has used for multi-hop networks for network division into various subareas. The main objective of this paper is creating a dynamic sub-area tree infrastructure for Mobile Ad hoc Networks (MANET). The proposed architecture uses the hierarchical procedure to divide the whole network into many geographical sub-area networks. In addition, each sub-area has a selected root node, we can configure the root node manually due to small ad hoc network and uses auto-discovery procedure to select the roots for large networks. The root node is located at the center of sub-area with hop level zero. The root function is used to update the routing table and root table for sub-area. After sub-area created any interconnected node detects a new inefficient node for sending the invitation message to join the sub-area tree. In the same sub-area, proactive routing protocols are used between the sub-area root node and its interconnect nodes and reactive routing protocols are used between all sub-areas root nodes. The new sub-area tree provides an infrastructure to avoid the flooding procedures. Routing in the sub-area tree avoids the transmission collision to optimize the ad-hoc networks.Â Â